2021
DOI: 10.3389/fpls.2021.768197
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Genetic Transformation: An Overview of the Current Strategies and Insights on the New Emerging Technologies

Abstract: Citrus are among the most prevailing fruit crops produced worldwide. The implementation of effective and reliable breeding programs is essential for coping with the increasing demands of satisfactory yield and quality of the fruit as well as to deal with the negative impact of fast-spreading diseases. Conventional methods are time-consuming and of difficult application because of inherent factors of citrus biology, such as their prolonged juvenile period and a complex reproductive stage, sometimes presenting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 220 publications
(333 reference statements)
0
8
0
5
Order By: Relevance
“…However, it should be noted that agrobacterium infiltration is not used widely in citrus due to its low efficiency, therefore, there is a need for a more robust transient expression system in citrus leaves 44 , 45 . Additionally, the stable expression of scFvH6 in plants can help prove the ability of this antibody to control Xcc , which requires a time- and labor-intensive procedure and may not be provided by agrobacterium-mediated transformation 46 . Hence, our findings can provide preliminary insight into the development of more tolerant plants to Xcc in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that agrobacterium infiltration is not used widely in citrus due to its low efficiency, therefore, there is a need for a more robust transient expression system in citrus leaves 44 , 45 . Additionally, the stable expression of scFvH6 in plants can help prove the ability of this antibody to control Xcc , which requires a time- and labor-intensive procedure and may not be provided by agrobacterium-mediated transformation 46 . Hence, our findings can provide preliminary insight into the development of more tolerant plants to Xcc in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, we failed to observe transgenic citrus lines for ProBs3 14EBE :avrGf1 (Shantharaj et al ., 2017) while we eventually identified one line containing the AvrGf2‐based Xcc‐TALE‐trap (Figure S2). The low overall transformation success rate might reflect the fact that the transformation of citrus is still challenging (Conti et al ., 2021). However, recent studies have shown that transgenic application of the rice executor gene Xa23 leads reduced bacterial growth, probably due to upstream promoters at the specific transgene integration site (Ji et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Citrus species can be transformed through different techniques ( Conti et al., 2021 ) ( Figure 3 ), although Agrobacterium -mediated gene transfer is the most commonly used transformation method ( Boscariol et al., 2006 ; Dutt and Grosser, 2009 ; Caserta et al., 2014 ; Souza-Neto et al., 2022 ). Different explants can be used to transform citrus species, mostly obtained from juvenile tissues, such as epicotyls and embryogenic cells, besides protoplasts ( Omar et al., 2007 ; Dutt et al., 2020 ; Li et al., 2022 ; Mahmoud et al., 2022 ; Su et al., 2023 ).…”
Section: Gene Editing Of Citrusmentioning
confidence: 99%